2015
DOI: 10.1021/acs.jpcb.5b09506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Compatible Solute Ectoine on the Local Water Structure: Implications for the Binding of the Protein G5P to DNA

Abstract: Microorganisms accumulate molar concentrations of compatible solutes like ectoine to prevent proteins from denaturation. Direct structural or spectroscopic information on the mechanism and about the hydration shell around ectoine are scarce. We combined surface plasmon resonance (SPR), confocal Raman spectroscopy, molecular dynamics simulations, and density functional theory (DFT) calculations to study the local hydration shell around ectoine and its influence on the binding of a gene-5-protein (G5P) to a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 73 publications
7
70
0
Order By: Relevance
“…36 Ectoine is known to be expelled from the first hydration shell of charged surfaces and biomolecules. 6,7,11 However, its presence in solution will inevitably decrease the amount of water around DNA in the biologically relevant target volume of 10-15 nm diameter. 20,37 Therefore, ectoine may act as a protective agent by passively displacing water from the surroundings of the DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Ectoine is known to be expelled from the first hydration shell of charged surfaces and biomolecules. 6,7,11 However, its presence in solution will inevitably decrease the amount of water around DNA in the biologically relevant target volume of 10-15 nm diameter. 20,37 Therefore, ectoine may act as a protective agent by passively displacing water from the surroundings of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…3) in the solid 4 state and in water, 5 exerts a kosmotropic effect on the local water structure [5][6][7][8] as well as an influence on protein functions. 7,[9][10][11] Moreover, various studies [12][13][14] investigated the effects of ectoine on biological damage caused by ultraviolet radiation (UV) of various wavelengths. The study by Bünger et al 13 found that UV-A (340-400 nm) irradiated human keratinocytes show a decrease in mitochondrial DNA mutations for cells pretreated with ectoine.…”
Section: Introductionmentioning
confidence: 99%
“…33 Although being attractive due to its simplicity, recent articles demonstrated the limitations of this concept in terms of concentration dependent binding effects for denaturants 15,31,34 or well-known protein protectants that indeed induce denaturation. 35,36 Henceforth, the chemical properties of solutes and osmolytes have to be studied in more detail for a deeper understanding of the resulting accumulation behavior. [37][38][39][40] The properties of osmolytes and their influence on PNIPAM were already discussed in a series of publications.…”
Section: Introductionmentioning
confidence: 99%
“…Halomonas elongata , an ectoine‐producing strain, has widely been studied, and recycled to develop the fermentation technology at large scale (Hahn et al . ). Optimal production of ectoines was conditioned by the interplay of carbon and nitrogen metabolism.…”
Section: Introductionmentioning
confidence: 97%